The significance of the conchiliofauna in the strategraphical and paleogeographical research of the Paleogene of platform Ukraine - KYSELEVYCH, L.; KUSHKA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The critical analysis of the published lists of fauna fossils of mollusks from Paleogene sediments of platform part of Ukraine is carried out. The role and key value of malacofauna of these complexes are established.